2020
DOI: 10.3389/fmicb.2020.00069
|View full text |Cite
|
Sign up to set email alerts
|

Oral Administration of Heat-Treated Lactobacilli Modifies the Murine Microbiome and Reduces Citrobacter Induced Colitis

Abstract: Significant evidence supports a relationship between the gut microbiome, inflammation, host response, and health, including the finding that a number of disorders are associated with disruption of the microbiome. In these disorders, a number of dietary interventions (including prebiotics, live probiotics, or heat-killed microbes) have been proposed to be curative or preventative agents. The use of heat-killed microbes has a number of benefits over living organisms, including reduced infection risk in vulnerabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 77 publications
0
16
1
Order By: Relevance
“…The study found that less abundant taxa were most affected. The same research group went on to use the same postbiotic in a mouse model of Citrobacter -induced colitis, which is characterized by a shortening of the small intestine and an increase in colon crypt depth 121 . The postbiotic did not prevent Citrobacter infection, but postbiotic-fed mice had a longer small intestine and reduced colon crypt depth compared with control animals that received standard mouse chow alone.…”
Section: Health Benefits Of Postbioticsmentioning
confidence: 99%
“…The study found that less abundant taxa were most affected. The same research group went on to use the same postbiotic in a mouse model of Citrobacter -induced colitis, which is characterized by a shortening of the small intestine and an increase in colon crypt depth 121 . The postbiotic did not prevent Citrobacter infection, but postbiotic-fed mice had a longer small intestine and reduced colon crypt depth compared with control animals that received standard mouse chow alone.…”
Section: Health Benefits Of Postbioticsmentioning
confidence: 99%
“…Murine studies have shown the effect of postbiotics on gastrointestinal mucosa in a Citrobacter -induced colitis model [ 266 ], whereas the mechanistic impact on mucosal inflammation in humans is more limited to specific metabolites such as butyrate as in the case of diversion colitis [ 267 ]. However, clinical studies focussing on subjective outcomes such as symptom scores have shown benefit of postbiotics in IBS [ 268 ].…”
Section: Microbiota-targeted Therapiesmentioning
confidence: 99%
“…Furthermore, viable probiotics reaching the colon must also manage to colonize the intestinal mucosa in competition with the indigenous bacteria ( Zmora et al., 2018 ). Interestingly, several reports demonstrated that many of the effects obtained from viable cells of probiotics can also be realized from the dead probiotics ( Adams, 2010 ; Li et al., 2016 ; Warda et al., 2019 ; Warda et al., 2020 ). Since this review mainly concentrate on the adhesion-associated surface molecules, the detailed part of dead probiotics and their function will not be described here.…”
Section: Introductionmentioning
confidence: 99%